Inhibitory effects of sesamin on human osteoclastogenesis - Orawan Wanachewin (2018)
© 2017, The Pharmaceutical Society of Korea. The promotional nature of sesamin on human osteoblast differentiation has been proven. Here, the effect of sesamin on human osteoclasts was investigated in terms of differentiation and function in M-CSF and RANKL induced human PBMCs. Sesamin treatment significantly decreased the number of differentiated osteoclasts observed by TRAP staining; however, sesamin inhibition did not result from the alteration of precursor cell proliferation. Sesamin did not decrease NFATc1 gene expression, which opposed the decreasing trend of CathK and TRAP expression. DC-STAMP, but not Atp6v0d2, also significantly decreased in the presence of 14 µM sesamin. Expressions of CCR2b and CCR4 as chemokine receptors were significantly down-regulated. Sesamin might mediate the inhibition of human osteoclast differentiation, the recruitment of precursor cells and F-actin formation. Decrease in the area of the resorption pits and the collagen released from the bone slices under sesamin treatment emphasized the inhibitory effects on both the differentiation and function of osteoclasts. Sesamin is a promising phytochemical agent inhibiting osteoclast differentiation and function.